2019
DOI: 10.1111/bju.14813
|View full text |Cite
|
Sign up to set email alerts
|

The global prevalence of erectile dysfunction: a review

Abstract: Objective To evaluate the global prevalence of erectile dysfunction (ED); as well as its association with physiological and pathological ageing by examining the relationship between ED and cardiovascular disease (CVD), benign prostatic hyperplasia (BPH), and dementia. We also aimed to characterise discrepancies caused by the use of different ED screening tools. Methods The Excerpta Medica dataBASE (EMBASE) and Medical Literature Analysis and Retrieval System Online (MEDLINE) were searched to find population‐ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
128
0
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(152 citation statements)
references
References 70 publications
7
128
0
17
Order By: Relevance
“…14 All data were extracted, independently checked for accuracies and analysed using Microsoft Excel and SPSS V21. In the most deprived regions, the yearly increases in prescription items were 9% in 2016, 4.5% in 2017 and 4.4% and 5.0% in 2018 and 2019 respectively. An overall 25% increase in prescription items was observed from 2015 to 2019.…”
Section: Data Collectionmentioning
confidence: 96%
See 2 more Smart Citations
“…14 All data were extracted, independently checked for accuracies and analysed using Microsoft Excel and SPSS V21. In the most deprived regions, the yearly increases in prescription items were 9% in 2016, 4.5% in 2017 and 4.4% and 5.0% in 2018 and 2019 respectively. An overall 25% increase in prescription items was observed from 2015 to 2019.…”
Section: Data Collectionmentioning
confidence: 96%
“…2 A systematic review reported that men with ED have an increased risk of all-cause mortality [OR 1.26; 95% CI, 1.01-1.57] and CVD mortality [OR 1.43; 95% CI, 1.00-2.05]. 4 The global prevalence of ED has been estimated to range from 3% to 76.5%. 4 A significant number of patients are known to suffer in isolation and do not seek help.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erectile dysfunction (ED) is defined by the permanent or recurrent inability to achieve or maintain a penile erection adequate for sexual intercourse [1]. Its global prevalence has been esteemed up to 76.5%, being higher with increasing age [2].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the BJUI remains your global journal . We present an excellent epidemiological paper on erectile dysfunction, a worldwide problem, which is a must read for every practising urologist . We also focus on prostate cancer in Peru , where it is an increasing problem especially in the coastal regions .…”
mentioning
confidence: 99%